PERAN PROMOSI EKSPOR INDONESIAN TRADE PROMOTION CENTRE (ITPC) CHICAGO DALAM PERDAGANGAN BILATERAL INDONESIA â€“ AMERIKA SERIKATTAHUN 2009-2014 - Halifa Haqqi, Athfinda Widi Hapsari & (Transformasi, 2015)
This research entitled â€œthe role of export Promotion by Indonesian Trade PromotionCentre (ITPC) Chicago in bilateral trade between Indonesia â€“ United States in 2009-2014â€.This research is motivated by the declining number of Indonesian non-oil exports tothe United States after the global economic crisis that hit the US causing the Indonesiangovernment in this case the Ministry of Commerce had to intervene to deal with thissituation because the US is a large market share for Indonesian exporters.The reasearhmethod used is descriptive qualitative, where the reseacher describe and outline therelevant data in the study and then the data for the subquent reduction is presented andverified in order to obtain valid result related research , data collection techniques usinginterviews and literature study, data sources using primary and secondary.From theseresults it can be conluded that the Indonesian Trade Promotion Centre is therepresentative body of the Ministry of Commerce of the Republic of Indonesia abroad,which aims to help bridge the trade relations between Indonesia and destination countriesplacement (Chicago, USA) was instrumental in improving Indonesia-US bilateral trade in2009-2014. Proven with rising trade balance Indonesia's non-oil exports to the US in2009-2014.Key Word : Indonesian Trade Promotion Centre Chicago, Promotion, BilateralTrade, non-petroleum